Anion conducting methylated aliphatic PBI and its calculated properties. Issue 3 (2nd November 2016) - Cho, Hyeongrae; Henkensmeier, Dirk; Brela, Mateusz; Michalak, Artur; Jang, Jong Hyun; Lee, Kwan‐Young
ABSTRACT: A methylated polybenzimidazole with an aliphatic chain in the backbone (Me‐PBI‐C10) was synthesized and formed into membranes. Literature suggests that alkyl chains on C2 of imidazolium ions increase their alkaline stability. While this may be true for model compounds or ions attached as a side chain, both our DFT calculations and experimental results show that Me‐PBI‐C10 does not withstand alkaline conditions. To increase the alkaline stability, blend membranes with PBI‐OO were fabricated. A blend membrane with 50% PBI‐OO showed a chloride conductivity of up to 6 mS/cm, indicating that these membranes could find use in non‐alkaline applications like vanadium redox flow batteries (VRFB). The high mechanical stability (tensile strength: 70.25 ± 14.85 MPa, Young modulus: 1.65 ± 0.16 GPa) would be an advantage over currently used Nafion membranes. Finally, three different models were successfully applied to qualitatively predict the water uptake of Me‐PBI‐C10 exchanged with different anions. The results match with experimental data. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 256–265 Abstract : A methylated polybenzimidazole with an aliphatic chain in the backbone (Me‐PBI‐C10) was synthesized and formed into anion conducting membranes. DFT calculations give insights into the cation/anion interactions, which are essential for the chemical stability of this class of polymers, and three models were applied to assess the polymer solvation, which can be tuned by the choice of anion. It is shown that the calculated and experimental values follow the same trend.